Crumpled hearts - Crain, Patricia Ann (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
A middle-aged woman, living in Johannesburg, has an experience which catapults her into changing her life. In the process of confronting her alcoholism, she realizes how patterns of addiction extend to other areas of her life and tries to make sense of the tragic events that have occurred. Her world becomes a different place as she questions everything that she has been taught about relationships, religion, race and her place in society. In the search for answers she uncovers stories about the lives of her parents, grandparents, relatives, friends and acquaintances. Embarking on a journey of discovery and rediscovery through her experiences and those of others, she explores the ways in which the things that she thought she knew defined her behaviour and expression of herself.
Keywords: South African fiction (English) -- 21st century; Creative writing (Higher education); English language -- Writing; South African fiction (English) -- Study and teaching (Higher)